2020
DOI: 10.1101/2020.06.01.127282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripersonal and reaching space differ: evidence from their spatial extent and multisensory facilitation pattern

Abstract: Peripersonal space is a multisensory representation of the space near body parts facilitating interactions with the close environment. Studies on non-human and human primates converge in showing that peripersonal space (PPS) is a body-part-centred representation that guides actions.Because of these characteristics, growing confusion conflates peripersonal and arm-reaching space (ARS) that is the space one's arm can reach. Despite neuroanatomical evidence favors their distinction, whether PPS and ARS tap into d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…Our results suggest that at least partially separate parietofrontal networks could be at play in anticipating motor or tactile events experienced by others. In a similar manner, employing a set of psychophysical tasks, Zanini et al [ 23 ] argued that the peripersonal space and the within arms' reach space representations are not superimposable. Studies using EEG [ 46 ], TMS [ 47 ], and fMRI [ 6 , 43 , 48 ] have confirmed that a multisensory representation of peripersonal space takes place in both the parietal and prefrontal areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that at least partially separate parietofrontal networks could be at play in anticipating motor or tactile events experienced by others. In a similar manner, employing a set of psychophysical tasks, Zanini et al [ 23 ] argued that the peripersonal space and the within arms' reach space representations are not superimposable. Studies using EEG [ 46 ], TMS [ 47 ], and fMRI [ 6 , 43 , 48 ] have confirmed that a multisensory representation of peripersonal space takes place in both the parietal and prefrontal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as suggested by recent behavioral studies, the networks in the brain coding for the space of action (“arm reaching space”) and the peripersonal space could be at least partially segregated. An important finding is that the space within arms' reach is not body part centered, while the peripersonal space is [ 23 ]. As a consequence, the predictive coding signatures associated with each of these two networks might also differ.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other measures have been proposed to capture a basic form of near-far differentiation in spatial processing, such as the line bisection task Lourenco, 2006, 2007) and reachability judgements (Costantini et al, 2010;Cardellicchio, Sinigaglia and Costantini, 2011;Delevoye-Turrell, Vienne and Coello, 2011). However, these tasks based on reachability judgments capture a larger, shoulder-centered representation of the reaching space that is distinguished from a multisensory body-parts-centered PPS representation sustaining both proactive and defensive behaviors (De Vignemont et al, in press;Zanini et al, 2020).…”
Section: Tasks To Evaluate Body Representationsmentioning
confidence: 99%
“…Previous studies have suggested that the space domain is divided into near (within the range of the arm) and far (beyond the range of the arm) spaces based on the hand-reaching distance 5,8,9 . According to the perception/action modal, the dorsal stream is implicated in near-space processing when individuals conduct an action and manipulation representation, and the ventral stream is implicated in far-space processing when individuals conduct a perception representation [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%